Manajemen Layanan Perpustakaan untuk Peserta Didik di SD Islam Terpadu Nurul Iman Palembang - Nurul Hidayah (Studia Manageria, 1970)
The results based on the data analysis can be concluded that the management planning of library services to participants in SD Isam diidk Nurul Iman Palembang done by providing infrastructure in the form of location and space, library collections, library manager (SDM) and circulation services. Implementation of the management of library services for students in elementary ISAM Nurul Iman Palembang evidenced from implementation planning, where locations are located on the floor 2, strategic, and noisy. The room was clean, noisy, accommodating 20 students and conducted in one room. Total collection of 3465 books. Business being friendly, berahlakul karimah and knowledgeable. The borrower and repayment is done by a process of open, closed, issuing membership cards, bring a book and check the time limit. Management's evaluation of library services for students in elementary ISAM Nurul Iman Palembang done by looking at the arrangement of space located on the floor 2, the left-right angle between the rack and the card, opposite side of the computer and reading table. Cleanliness of floor space, chairs, desks, collections, shelves of old books were not clean. Collection of the most desirable 13 fiction and 13 non-fiction. Behavior being polite, responsible, knowledgeable enough. Data visitors numbered 20 students and books borrowed amounted to 26 books.